ANALYSIS AND DESIGN WEBSITE FOR STUDENT MANAGEMENT SYSTEM IN BIDIK MISI PROGRAMME BASED ON WEB 2.0 (CASE STUDY IN STUDENT AND ACADEMIC OFFICE, UNIVERSITY OF PALANGKA RAYA) - Abertun Sagit Sahay; Rony Teguh; Rino Franando; Asep Engku Izzuddin (Universitas Palangka Raya, 2016)
Bidik MISI is a scholarship program to student in high school for continue in private University all Indonesia. The scholarship are given to students have excelent grade and ability cost to continue in University. The candidate of student must be evaluate every season of academic program in University. If the value of grade student can not pass from threshold of University system. The student have a warning and the scholarship can be stoped. In this thesis, The system needed for evaluate of grade GPA every student and the system can delivery of information to citizen and student.The Method of ADKI (Analysis, Design, Code, and Implementation) is adaptive method from waterfall, iterative, incremental, and spiral. The method used for system analysis into website system for develop of framework of application. In the ADKI method have three phase to design a software engineering. Analysis of information data and management grade GPA of students in use phase 1 that is analysis and design.In this thesis, Analysis and Design for system is done, We are continue to phase design and code and code and implementation.